What Motivates the Gold Traders to Fulfill Zakat on Gold Compliance? Discovering the Internal and External Factors - Virgiawan, Rheyza; Al-Qudry, Anas; Pusparini, Martini Dwi (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2023)
Zakat is an obligatory charitable giving that holds immense significance in the lives of Muslims worldwide. While zakat is primarily associated with financial assets, such as money and agricultural produce, one specific aspect often overlooked is Zakat on gold. This study attempts to discover what factors shape the perception of gold traders towards fulfilling gold zakat compliance. In this study, primary data was collected from 18 gold traders at Lambaro Ingin Jaya Market, Aceh Besar, through in-depth interviews. The study discovered that the perception of gold traders at Lambaro Market, Ingin Jaya, Aceh Besar, regarding the fulfillment of zakat on gold is motivated by a combination of internal and external factors. The internal factors encompass elements such as attitude, level of faith, knowledge, awareness, self-satisfaction, and moral values driven by the desire to seek the pleasure of Allah SWT. Conversely, external factors consist of educational elements, social values inherent in zakat, and the level of trust placed in amil zakat institutions. Additionally, the perception towards zakat on gold compliance is influenced by inhibiting and supporting factors. Inhibiting factors encompass statutory policies, traditional attitudes, and the impact of the Covid-19 Pandemic. In the other hand, supporting factors involve the awareness of gold traders in fulfilling zakat obligations and their altruistic or socially sensitive inclinations.